2009
DOI: 10.1128/jcm.02099-08
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Human Immunodeficiency Virus Type 1 (HIV-1) RNA Measurements Obtained with Dried Blood Spots and Those Obtained with Plasma by Use of Nuclisens EasyQ HIV-1 and Abbott RealTime HIV Load Tests

Abstract: The plasma human immunodeficiency virus (HIV) RNA load is used in the clinical routine for the monitoring of HIV infection and the patient's response to antiretroviral therapy. Other body fluids or dried blood spots (DBS) can be used, however, to assess the level of viremia. The use of DBS may be especially helpful for the monitoring of HIV-infected patients in resource-poor settings, where access to adequate laboratory facilities is often difficult. However, the correlation between the HIV RNA levels in plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 33 publications
7
60
1
Order By: Relevance
“…However, automation of the procedure may improve agreement between the results obtained testing DBS and plasma due to the reduced human intervention, lower risk of cross contamination, and more rapid turnaround time. In our current study, the correlation between the VL measurements in plasma and DBS was satisfactory and was superior to the results obtained previously using manual RNA nucleic acid isolation (11).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…However, automation of the procedure may improve agreement between the results obtained testing DBS and plasma due to the reduced human intervention, lower risk of cross contamination, and more rapid turnaround time. In our current study, the correlation between the VL measurements in plasma and DBS was satisfactory and was superior to the results obtained previously using manual RNA nucleic acid isolation (11).…”
Section: Discussionsupporting
confidence: 66%
“…A previous study showed that manual RNA nucleic acid isolation using the Abbott mSample preparation system resulted in good correlation compared with automatic procedures (11). However, automation of the procedure may improve agreement between the results obtained testing DBS and plasma due to the reduced human intervention, lower risk of cross contamination, and more rapid turnaround time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sensitivity of dried blood spots for viral load determination at this threshold may be reduced (210,211). Programmes relying on dried blood spot technology for viral load assessment may therefore consider retaining the higher threshold (3000-5000 copies/ml) until sensitivity at lower thresholds is established (212-214).…”
Section: Threshold For Defining Virological Failurementioning
confidence: 99%
“…Multiple studies have also explored the possibility of transporting dried blood or plasma specimens from more primitive sites to a capable laboratory as a global health solution for plasma viral load testing, though this does not address the ultimate need for a rapid, PoC test [21]- [24]. Progress toward viral load in resource-limited settings has emerged in the form of assays for other biomolecular components of HIV, including the structural capsid protein p24 and the enzyme reverse transcriptase (RT), platforms aimed at the miniaturization of the amplification and/or detection aspects of nucleic acid quantification, and isolation of whole viruses from blood samples as a processing step toward direct particle counting.…”
Section: A Current State Of the Artmentioning
confidence: 99%